2021
DOI: 10.1017/s0003055420001124
|View full text |Cite
|
Sign up to set email alerts
|

When Unfamiliarity Breeds Contempt: How Partisan Selective Exposure Sustains Oppositional Media Hostility

Abstract: Partisans hold unfavorable views of media they associate with the other party. They also avoid out-party news sources. We link these developments and argue that partisans assess out-party media based on negative and inaccurate stereotypes. This means cross-cutting exposure that challenges these misperceptions can improve assessments of out-party media. To support this argument, we use survey-linked web browsing data to show that the public has hostile views of out-party news sources they rarely encounter. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 79 publications
1
13
0
1
Order By: Relevance
“…As we consider media outlet reputations, our framework is also helpful for studying the origins of hostile attitudes towards political news media and our evidence aligns with other accounts about the role of attacks from political elites, more so than any negative responses to news coverage itself, in generating antipathy towards the media (Ladd 2010, Archer 2020, Peterson and Kagalwala 2021.…”
Section: Discussionsupporting
confidence: 58%
“…As we consider media outlet reputations, our framework is also helpful for studying the origins of hostile attitudes towards political news media and our evidence aligns with other accounts about the role of attacks from political elites, more so than any negative responses to news coverage itself, in generating antipathy towards the media (Ladd 2010, Archer 2020, Peterson and Kagalwala 2021.…”
Section: Discussionsupporting
confidence: 58%
“…Second, research on political perceptions shows that partisans tend to believe supporters of the rival party hold more extreme partisan views [13,14] and stereotypical qualities [15] than they do in reality. This pattern is thought to be driven, at least in part, by partisan media environments that highlight negative and extreme views of the outparty [16,17,18,19,20,21]. Inaccurate perceptions of rival partisans could lead Americans to believe outpartisans have more extreme views about supporting and engaging in partisan violence than they do in reality.…”
Section: Introductionmentioning
confidence: 99%
“…These behaviors have been explained by selective exposure theory and confirmation bias in social sciences. Other works have found that reinforcement of strong beliefs is weaker in individuals with moderate viewpoints, or in case of two-sided neutral debates and cross-cutting exposure [21,27,43], as explained by social science concepts like moderation theory and cross-cutting discussions.…”
Section: Related Workmentioning
confidence: 99%
“…The exchange of ideas among people with politically dissimilar groups is known as cross-cutting discussions. Research in this field has shown that awareness of rationales for oppositional viewpoints increases with the exposure to disagreement, and that affective polarization is negatively related to involvement in cross-cutting discussions [37,43]. This implies that greater network diversity reduces polarization by facilitating cross-cutting discussions.…”
Section: Related Workmentioning
confidence: 99%